Tubulin flux at spastin-induced nanodamage sites regulates microtubule rescue frequency and EB1 lifetimes - Ewa Szczesna; Jeffrey O. Spector; Stephanie L. Sarbanes; Jiayi Chen; Agnieszka Szyk; Antonina Roll-Mecak (Proceedings of the National Academy of Sciences, 2026)
Severing enzymes nanodamage microtubules by extracting tubulin subunits. This extraction is accompanied by spontaneous repair with soluble tubulin. Here, we show that GTP-, and not GDP–tubulin, incorporates preferentially at nanodamage sites where it recruits end binding protein-1 (EB1). Using GTP hydrolysis-defective recombinant tubulin mutants we show that the tubulin GTPase is a timer for EB1 association at repair sites. Tubulin on-rate controls both the size and lifetime of the spastin-catalyzed GTP-islands which promote rescues. Consistent with this, first, rescue rates in the presence of repair vary steeply with tubulin concentration, unlike in the absence of repair, and second, spastin-catalyzed lattice remodeling, and not passive binding of the enzyme alone, increases rescue rates. Furthermore, we show that, when overexpressed at low levels in cells, spastin catalyzes microtubule repair and affects microtubule growth. Thus, microtubule severing proceeds through GTP–tubulin repair intermediates both in vitro and in cells. Our work demonstrates that severing enzymes exert their effects on microtubule function through tubulin extraction and repair and strongly supports microtubule dynamics regulation through tubulin dimer exchange along the lattice.